ENHANCEMENT OF OPERATING EFFICIENCY OF THE NATIONAL MEDICAL HOLDING THROUGH CENTRALIZATION OF FINANCIAL FUNCTIONS AND CASH FLOWS - Yezhov, Vladislav (Nazarbayev University Graduate School of Business, 2016)
This paper explores financial management problems in the medical holding company, which has more control over their expenses than income. At the same time the parent company does not provide medical services and does not have stable sources of revenue to cover the maintenance costs of its staff. Each subsidiary of the holding company may carry out medical activities on their own, however the economy of scale can optimize administrative costs, save money on procurement and improve operating processes in clinics of holding company...
Thesis
Keywords: medical holding company; financial management problems